Impact of Disclosure Level in the Cost of Capital of Brazilian public companies of Civil Construction Sector - Bizelli, Juliana Sahão; Albuquerque, Andrei Aparecido de; Souza, Kamyr Gomes de (Revista de Administração da UFSM, 2017)
This research aimed to analyze the effect of disclosure level on the cost of capital of Brazilian public companies of construction sector. Basically, this study aimed to validate the negative relationship between the variables in the Brazilian capital market, as in international markets. The methodology used was quasi-experimental research the type ex post facto, applying multiple linear regression with panel data. In the results wasn’t found significant relationship between disclosure and cost of capital. So it wasn’t provided the negative relationship express by the theory between disclosure level and cost of capital in this business segment in the analyzed period.